Physical Activity Surveillance Using Wearable Activity Monitors: Are US Adults Willing to Share Their Data?. Issue 6 (July 2020) - Hyde, Eric T.; Omura, John D.; Fulton, Janet E.; Weldy, Andre; Carlson, Susan A.
Purpose: Wearable activity monitors (wearables) have generated interest for national physical activity (PA) surveillance; however, concerns exist related to estimates obtained from current users willing to share data. We examined how limiting data to current users who are willing to share data associated with PA estimates in a nationwide sample. Design: Cross-sectional web-based survey. Setting: US adults. Subjects: In total, 942 respondents. Measures: The 2018 Government & Academic Omnibus Survey assessing current wearable use, willingness to share data with various people or organizations, and PA levels. Analysis: Estimated the prevalence of current wearable use; current users' willingness to share data with various people or organizations; and PA levels overall, among current users, and among current users willing to share their data. Results: Overall, 21.7% (95% confidence interval [CI]: 19.1-24.5) of US adults reported currently using a wearable. Among current users, willingness to share ranged from 40.1% with a public health agency to 76.3% with their health-care provider. Overall, 62.2% (95% CI: 58.9-65.3) of adults were physically active. These levels were similar between current users (75.0%, 95% CI: 68.3-80.7) and current users willing to share their data (75.3%, 95% CI: 67.9-81.5). Conclusion: Our findings suggest that using data from wearable users may overestimate PA levels, although reported willingness to share the data may not compound this issue.